(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper provides a temptative analysis of the two extant Palaeo-Hispanic mosaic inscriptions from the middle Ebro valley. Their lexical correspondences and morphological divergences might be accounted for if we assume that an antipassive construction occurs in the inscription from Andelos. Antipassive derivations are common in ergative languages and in previous studies it had been argued that Iberian must have been a language of this type. From an areal perspective, it is also remarkable that evidence of antipas-sive constructions may be found in Basque, too. Iberian and Basque must have been in contact in Antiquity and typological studies have shown how antipasive constructions tend to cluster genetically and areally.